Persepsi Masyarakat terhadap Mitos Larangan Nanggap Wayang dan Nggantung Gong di Desa Tulungrejo, Kecamatan Pare, Kabupaten Kediri - Setyowati, Asri; Laksmiwati, Ida Ayu Alit; Aliffiati, . (Sunari Penjor : Journal of Anthropology; Vol 8 No 1 (2024): Volume 8. No. 1. Maret 2024DO - 10.24843/SP.2024.v8.i01.p03, 2024)
The people of Tulungrejo Village believe that they are not allowed to inviting wayang and hanging the gong because this can bring disaster. The purpose of this research is to understand the reason why people still maintain these myts and to find out how people interpret the wxistence of these myths. The theory used is theory of semiotics from Charles Pierce and structural theory from Lévi-Strauss to find out the meaning of the myth of the prohibition of inviting wayang and hanging gongs in the life of the people of Tulungrejo Village. This study used a qualitative research method with an ethnographic research model through observation, interview techniques and literature study. Based on the results of the research that has been done, there are reasons why people still believe in and maintain the myth of the prohibition of inviting wayang and hanging gongs because hese myths useful values and functions for the people of Tulungrejo Village: 1) as acommunity effort to avoid unwanted disaster, 2) as a means of delivering ethics education messages, and 3) as a medium for sreading Islam.